Oil Cakes as Sustainable Agro‐Industrial Feedstock for Biocarbon Materials. Issue 1 (16th December 2021) - Siva Sankari, M.; Vivekanandhan, S.; Misra, M.; Mohanty, A. K.
Abstract: The demand for vegetable oil is increasing for both food and non‐food applications, which leads to the generation of a huge amount of oil cakes. The rising annual production requires alternative applications for sustainable operations of oil mills, especially those involved in non‐edible oil production. Hence, the value‐added uses of oil cakes such as environment remediation (metal absorption), composite fabrication (as fillers, reinforcements), nanoparticle synthesis (as reducing and stabilizing agent), and production of carbonaceous materials (as carbon source) were extensively explored in recent years. Among them, the thermochemical conversion of oil cakes into carbonaceous materials (biochar and activated carbon) received great interest as the demand for biocarbon materials increases exponentially. Oil cake‐derived biocarbon materials found a wide range of technological applications. With this perspective, recent developments in oil cake‐derived carbon materials and their diverse applications are reviewed. Abstract : The ever increasing vegetable oil production generates huge amounts of oil cake residues. Value addition to these oil cake residues is essential for the sustainability of oil industries. Biocarbon production is one of the emerging and key applications for oil cake residues. The recent progresses and developments in oil cake‐derived biocarbons and their applications are reviewed and discussed.